Representations of orientals in selected novels by Marmaduke Pickthall - Akhter, Bilkis; Mohd Ramli, Aimillia (IIUM Press, International Islamic University Malaysia, 2017)
Marmaduke Pickthall (1875-1936) is known mostly as a translator of the meaning of the Qur’an but his fictional outputs are rarely acknowledged and, consequently, are much less studied. This book aims to address this imbalance by analysing five of his selected novels in chronological order starting with Said the Fisherman (1903), followed by The House of Islam (1906), Veiled Women (1913), The House of War (1916) and, finally, The Early Hours (1921). Applying the theoretical framework that Edward Said (1935-2003) had established in his monumental book, Orientalism (1978), this study seeks to discover the various ways in which Pickthall negotiated his support for British colonialism with his desire to see the Ottoman Empire restored. This book argues that Pickthall’s sympathy towards the Muslims and his indepth knowledge of Islamic teachings are reflected throughout the selected texts. The significance of this study also lies in the fact that it endeavours to connect the thematic concerns of the selected novels to pertinent issues that are still relevant in today’s world such as veiling, polygamy and the position of non-Muslim minorities in Muslim-majority countries. It also shows that the selected novels invite readers to ponder on the causes for the calamities that had befallen Muslims during the early twentieth century that are unfortunately still prevalent in today’s world. Finally, this study suggests that Pickthall’s narratives indicate that the best ways for the Muslims to overcome their problems are through being united as well as developing tolerance and mutual respect for other peoples from different racial and religious backgrounds.